Validity and reliability of the Turkish version of the Implementation Leadership Scale in the context of nurses - Ahmet Yıldız (BMC, 2024)
Abstract Background The implementation of evidence-based practices (EBPs) in healthcare is of critical importance, and nursing leadership plays a significant role in this process; however, there is a lack of validated instruments to measure the effectiveness of implementation leadership for EBPs. This study aims to evaluate the validity and reliability of the Turkish version of the Implementation Leadership Scale (ILS) within the context of nursing. Methods Data were obtained through a cross-sectional study. The original ILS was first translated into Turkish and then back into English. The scale was administered to 343 nurses working in a training and research hospital in Türkiye. Content validity was assessed with input from 10 experts. The data set was randomly divided into two subsamples to evaluate the construct validity of the ILS. Exploratory factor analyse (EFA) was conducted in sub-sample 1 (n = 172) and Confirmatory factor analyse (CFA) was conducted in sub-sample 2 (n = 171). Reliability was assessed using Cronbach's alpha values, test-retest reliability, item-total statistics, and split-half reliability. Results The content validity index was calculated to be 0.96, indicating high validity. EFA revealed that the scale consists of four factors with eigenvalues greater than 1, and these factors together explained a high proportion of the total variance (77.10%). Confirmatory factor analysis results (χ2 / df = 1.29; CFI = 0.98; GFI = 0.94; AGFI = 0.91; NFI = 0.94; RMSEA = 0.04) confirmed that the Turkish version of the ILS maintains the original four-factor structure (Proactive, Knowledgeable, Supportive, and Perseverant leadership). Cronbach's alpha values (0.80-0.88) and intraclass correlation coefficients (ICC) (0.78-0.86) were found to be high. Item-total correlations (0.38-0.63) and the Spearman-Brown coefficient (0.75) were above acceptable levels. Conclusion The findings suggest that the Turkish version of the ILS is a valid and reliable tool for assessing implementation leadership in evidence-based practice (EBP) among nurses. This version of the ILS could contribute to further research on implementation leadership in Türkiye, international comparisons of EBP leadership, and the development of EBP practices.